Pengaruh Biaya Pemeliharaan, Nilai taksiran, dan Kualitas Layanan terhadap Keputusan Nasabah Gadai Emas di Pegadaian Syariah KC Kusumanegara Yogyakarta - Aditiawati, Indah; Syah, Toufan Aldian (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of maintenance costs, estimated value and service quality on customers' decisions to choose gold pawn products. The phenomenon related to the recent surge in world gold prices has had a significant impact on the pawnshop industry. In December 2023, the price of gold will reach a record high of IDR 1.14 million per gram. This trend of increasing gold prices during 2023 will affect the performance of gold pawn products, a financing practice that is well known in the community. Primary data for this research was obtained through distributing questionnaires to 100 customers of Pegadaian Syariah KC Kusumanegara. The research methods used include Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Determination Coefficient, t Test, and F Test. The research results show that: 1) maintenance costs have a significant effect on customer decisions; 2) the estimated value does not have a significant effect on customer decisions; 3) service quality has a significant effect on customer decisions. Overall, maintenance costs, estimated value, and service quality simultaneously influence customer decisions